Manajemen Stres di Kalangan Anak Muda Muslim: Peran Signifikan Agama dalam Mengelola Tekanan Psikologis - Yazid, Ahmad (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2024)
Young people, as a group vulnerable to stress, undergo a transition phase from adolescence to adulthood that introduces them to various pressures and new challenges significantly affecting their psychological well-being. In response to these challenges, they develop various coping strategies to manage issues and regulate their emotional state. This study aims to investigate the challenges and pressures faced by young Muslim individuals, as well as the coping strategies they employ. This research used a qualitative method with a phenomenological approach. Data for this study were obtained through interviews conducted with 21 young Muslim individuals (8 males and 13 females). The interview data were subsequently analyzed using thematic analysis. The findings indicate that young Muslims experience three main stress-inducing issues: personal problems, family issues, and financial difficulties. In tackling these challenges, they adopt diverse stress coping strategies. These coping strategies encompass religious and non-religious approaches that effectively help them manage stress. However, the research also identifies maladaptive coping strategies that do not assist them in effectively dealing with stress. Overall, this study provides insights into how young Muslims confront and respond to the pressures they encounter during the transition from adolescence to adulthood, offering strategic implications for improved psychological interventions and support.